Análisis de los procesos de crédito del almacén Victor Peñaloza de la ciudad de Pasaje, periodo 2015. - Agila Ordoñez, Roberto Jonhy (2017)
The modalities for credit have been evolving, generating new markets and new providers of this service, since financial institutions are no longer the only providers of monetary resources to cover the different needs of consumption or investment; This means that merchants of goods that occupy a large percentage in our economy open markets not only in the endowment of products but also in providing the service to finance the purchase. As in Ecuador, informal and consumer credit has a direct effect on the economy (Wilkis, 2014). In addition, commercial loans clearly have advantages, such as the non-presentation of assets as a guarantee of payment giving importance to the debtor, which unlike financial credits, collateral or mortgage are mandatory, with this gives access to a less competitive market And more humble, increasing the level of exchange of goods or services for money, Torres Moreno (2014) shares. Commercial credits are based on the granting of terms in the purchase of a good (the terms depend on the amount of the purchase and the economic solvency of the future debtor) in order to increase sales in exchange for greater risk by increasing the assets Current, that is to say, give payment facilities to those who do not leave us a good in exchange for the fact that we are left owing and believe that they are receivable, if, at the time, the appropriate credit policies were not applied to grant the credit, Which will become an uncollectible account that affects the liquidity of the business; Here is the importance of the study on commercial credit since it has influence on the macroeconomy of the countries (Grau Alfredo, 2014). For this reason, the analysis of a case that demonstrates the current reality about the small companies dedicated to the trade, analyzing the application of control and management tools represented in manuals and policies. In relation to this the main objective of this work is the analysis of the credit processes of the Warehouse Peñaloza of the city of Pasaje, that is dedicated to the retail sale of electrical appliances, motorcycles and computers, by means of the lifting of information using techniques Such as the interview, the survey, the observation sheet and the checklist. We conclude by presenting an in-depth analysis of each of the aspects involved in the credit process, such as credit management analysis, the mastery and use of financial ratios, types of collateral and collection procedures; Presenting their results in tables and graphs to later interpret the level of development they have in relation to their current management. The study of this case simply has many important aspects to study, although we will not be able to deepen all of them. I leave questions to them so that in future investigations they can be clarified, since the study of the processes of credit in the commercial sector does not only cover Small Companies, are also medium and large and each with its special features.